PENGARUH KONSENTRASI PENGINDUKSI METANOL SERTA"SUMBER KARBON SORBITOL DAN MONITOL TERHADAP PRODUKSI a-AMILASE Saccharomycopsis fibuligera R64 DALAM Pichia pastoris - Shabarni Gaffar; Dani Permana; Diana P Rahmawati; Triana N Meirina; Abu Bakar M.I. Syihab; Safrl Ismayana; Toto Subroto; O Suprijana (Jurnal Kimia Terapan Indonesia, 2011)
Pichia pastoris has been widely used as host for heterologous protein expression for commercial purposes. The advantages of P. pastoris as protein expression host is its ability to grow with high cell density and the presence of a gene promoter that canbe induced tightly, named AOXI encoding alcohol oxidase. Improvement of recombinant protein production under control of AOXI promoter in P. pastoris expression system is still a major concern. Optimization of methanol concentration as inducerand addition of carbon sources, is one of the strategies to improve the expression level. This research aims to study the effect of methanol as inducer as well as sorbitol and mannitol as additional carbon source to the expression level of recombinantSaccharomycopsis fibuligera a-amylase (Sfamy) by P. pastoris (Mut). Sorbitol and manuot known as non-repressive carbon source, to increase the growth ofP. past oris, but not inhibit the AOX1 promoter and foreign proteins expression. Sfamy was expressed in P. pastoris GS115 (His-, Mut) with addition ofcarbon source, sorbitol and mannitol saparately to the expression medium. The result showed that, the optimum concentration" of methanol inducer for Sfamy production is 0.75%. The addition of sorbitol or mannitol increased Sfamy production. Concentrations of sorbitol and mannitol 2% with0.75% methanol inducer increase the secretion level of recombinant Sfamy 2.13 times and 1.94 times respectively, compared with no additional carbon source. This result indicated that addition of carbon source can improved recombinant protein production by P. pastoris, and the used of sorbitol as additionalcarbon source is more effective compared to mannitol.Key words: a-amylase. Pichid pastoris, methanol, sorbitol,mannitol.